Public contracts and good faith: the protection of citizen’s rights in the Peruvian administrative legal system - Cuba Meneses, Erick (Universidad Nacional del Litoral, 2018)
The purpose of this article is explain the causes and justifications for the application or non-application of penalties in Contracts regulated by Law N° 30225; Likewise, explains the limits that the Constitutional Court has indicated in the cases of contracts with abusive clauses applied in the public sector and the relation with the contractual good faith principle.